Thomistic and Vladimir Solovyev’s Ideas in Adomas Dambrauskas-Jakštas’ Philosophy - Šliogeris, Arvydas (Problemos, 1973)
The article discusses the influence of the philosophical views of Vladimir Solovyev, the Russian idealist philosopher of the late 19th century on Adomas Dambrauskas-Jakštas, a representative of the bourgeois Lithuanian neoscholastic philosophy. The author shows that a struggle between Solovyev’s ideas and thomism is characteristic of the philosophical views of the Lithuanian idealist philosopher. Thus Jakštas is to be considered neither a consistent thomist nor an orthodox disciple of Solovyev.